Precision immunointerception of EGFR-driven tumorigenesis for lung cancer prevention - Pan, Jing; Xiong, Donghai; Zhang, Qi; Palen, Katie; Shoemaker, Robert H.; Johnson, Bryon; Sei, Shizuko; Wang, Yian; You, Ming (Frontiers in Immunology, 2023)
Epidermal growth factor receptor (EGFR) mutations occur in about 50% of lung adenocarcinomas in Asia and about 15% in the US. EGFR mutation-specific inhibitors have been developed and made significant contributions to controlling EGFR mutated non-small cell lung cancer. However, resistance frequently develops within 1 to 2 years due to acquired mutations. No effective approaches that target mutant EGFR have been developed to treat relapse following tyrosine kinase inhibitor (TKI) treatment. Vaccination against mutant EGFR is one area of active exploration. In this study, we identified immunogenic epitopes for the common EGFR mutations in humans and formulated a multi-peptide vaccine (Emut Vax) targeting the EGFR L858R, T790M, and Del19 mutations. The efficacy of the Emut Vax was evaluated in both syngeneic and genetic engineered EGFR mutation-driven murine lung tumor models with prophylactic settings, where the vaccinations were given before the onset of the tumor induction. The multi-peptide Emut Vax effectively prevented the onset of EGFR mutation-driven lung tumorigenesis in both syngeneic and genetically engineered mouse models (GEMMs). Flow cytometry and single-cell RNA sequencing were conducted to investigate the impact of Emut Vax on immune modulation. Emut Vax significantly enhanced Th1 responses in the tumor microenvironment and decreased suppressive Tregs to enhance anti-tumor efficacy. Our results show that multi-peptide Emut Vax is effective in preventing common EGFR mutation-driven lung tumorigenesis, and the vaccine elicits broad immune responses that are not limited to anti-tumor Th1 response.